An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G.; Pignatti, S.; Testi, a (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2007)
Abstract The vegetation of the study site near Rome (Castelporziano Estate), where different woodland types occur, was analysed on the basis of ecological indicator values (Zeigerwerte) for light, temperature, continentality of climate, soil moisture, soil pH and nitrogen. Indicator values were estimated with Hill's reprediction algorithm for the flora of Central-Southern Italy relying on a database of 4,207 original relevés representing a balanced survey of the vegetation of this and surrounding areas. It was possible to obtain indicator values for an important fraction of the Italian Mediterranean flora. Results are ecologically reasonable, and it was possible to find strong correlation between the recalculated values and a few environmental variables. These correlations were not significant in an analogous test with subjectively derived scores of Ellenberg indicator values.
From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)From Duplicate 1 (An application case of ecological indicator values (Zeigerwerte) calculated with a simple algorithmic approach - Fanelli, G; Pignatti, S; Testi, A)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; Italy; reprediction algorithm; vegetation ecology

Edaphic characteristics of Quercus suber woods in Latium - Dowgiallo, G; Testi, a; Pesoli, P; Pignatti, S (Rendiconti Lincei, 1997)
{In this paper the results are reported of a soil survey done in selected sites of Latium un- der the most significant Quercus suber woods (Cytiso-Quercetum suberis Testi, Pignatti and Lucattini 1994) previously studied from a phytosociologicat point of view. After describing the dominant soil type of each area, physical-chemical characteristics have been analysed in order to point out the significance of edaphic factors in the distribution and floristic composition, of the Quereus suber co,noses. Bioclimatic, structural and edaphic features of this vegetation showed a great convergence; among all the parameters examined, AWC resulted to be the most effective one in conditioning the mesophilous character of Quercus suber coenoses growing in Latium. In this respect this type of vegetation shows rather strong affinities with mixed Quercztr cerrz} woods, both in the floristic composition and in the edaphic requirements, as already suggest- ed in the most recent phytosociological studies.
Keywords: Correlation soil-vegetation; Latium; Quercus suber oakwoods; soils

Contribution to the syntaxonomic knowledge of Quercus suber woodlands of Latium - Testi, a; Lucattini, C (Rendiconti Lincei, 1994)
This study is a contribution to the knowledge and syntaxonomic definition of Q. suber forests of the Latium region, which represent the last traces Of a forestal belt that at one time was certainly much more developed. In ten sites representative of the Q. suber vegetation, 33 relev& were taken using the Braun-Blanquet phytosociological method (1952). The matrix of 90 species x 33 retev& was placed un- der multivariate analysis (Wildi and Orloci, 1987). From the overall elaboration of the data, a structured table was obtained which allowed for an ecological and phytosociol0gical interpretation of the results. The Q suber woodlands of Latium were attributed to the new association Cytiso-Quercetum suberis, concentrat- ed in the subhumid belt and diffused on markedly acid soils.
Keywords: Latium; Quercus suber woodlands; Syntaxonomy